Molecular investigation of biofilm genes in Staphylococcus epidermidis - Jabbar Abosaooda , Lamyaa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Biofilms play a major role in antibiotic resistance, making the resulting infections difficult to treat. Biofilms are a key factor in the successful survival of bacteria in complex environments such as those inside the human body, where they can protect them from damaging environmental factors and immune attack. The aim of study was to investigate some of the genes that make the biofilm, determine their sequence. Blood samples were collected from 100 patients undergoing chronic hemodialysis at AL-Diwaniyah General Hospital. Samples were achieved aseptically applying sterile syringes by trained phlebotomists following standard infection control protocols to minimize contamination risks. The results showed that Electrophoresis showed that 10 isolate (66.66%) belonging to the S. epidermidis species possessed the atle gene with a molecular weight of 682 base pairs (bp). The aap gene with a molecular weight of 466 base pairs, 9 isolates (60%) of the S. epidermidis. Also, it notes that 4 isolates (25.66%) of S. epidermidis encoded the bhp gene with a molecular weight of 1083 base pairs, while there are 7 isolates (46.66%) of S. epidermidis that possess the icaA gene with a molecular weight of 188 base pairs (bp).